Aggressive Adenocarcinoma of the Cervical Esophagus: Importance of a Multidisciplinary Approach. (11th December 2012) - Fashoyin, Adedayo; Hartig, Gregory; Schelman, William R.; Ritter, Mark; Agni, Rashmi; Gopal, Deepak V.; Pfau, Patrick R.; Weiss, Jennifer M.
Abstract : Adenocarcinoma of the cervical esophagus is a rare tumor, in comparison to adenocarcinoma of the distal esophagus which is on the rise and is often associated with Barrett's esophagus. We present a case of aggressive cervical esophageal adenocarcinoma in a 46-year-old female with no endoscopic or histopathologic evidence of Barrett's esophagus. We discuss the possible etiology of this tumor and review the treatment options, highlighting the importance of a multidisciplinary approach to the management of this rare disease.